Perspectives of students - Future natural sciences teachers regarded teacher’s role as educator - Orce Mitevski; Katerina Mitevska Petrusheva; Biljana Popeska (SciencePark Research, Organization & Counseling, 2017)
One of the important segments in the initial education of the teachers is creating positive attitudes of students for the importance of teachers’ role as educator. The aim of this research is to determine the attitudes of students – future teachers about the role of the teacher as an educator and to determine the differences in student’s attitudes regarded their sex. The study was conducted on a sample of 94 examiners, students at Teaching Faculties in Republic of Macedonia preparing for future teachers in natural sciences. Obtained results were analyzed using quantitative and qualitative analyses. Differences in student’s attitudes regarded the sex were determined using Pearson chi - square test. It could be concluded that students-future teachers in natural sciences have developed positive attitudes toward teacher’s role as educator, establishing teacher’s personal characteristics, its authority, and reputation and building quality relations with pupils as one of the important aspect. Yet it’s notable that for most the examiners, the teacher’s role as a transmitter of knowledge is defined as more important and priority. These findings suggest on the need for greater emphasis on the teacher as a factor in creating a student’s personality through educational activities and realization of teacher’s role as educator
Keywords: Competences, pedagogical work, educator, students.